Final report of IPSR pellets workshop - Souissi, Asma; Maanai, Amal; Tebourbi, Ons; Shiri, Zahra; Ouerghemmi, Hassen (2023)
The report shows elements of the workshop including scaling ambition, innovation packaging, innovation readiness and use as well as scaling readiness.